Inquiry Inquiry-Based Approach in Biological Anthropology Education: Evidance of Early Bipedalism in Basal Hominins - Sumilih, Dimas Ario (Celebes Journal of Elementary Education, 2025)
This paper aims to analyze the effectiveness of the guided inquiry approach in enhancing students’ understanding of early bipedalism evidence in basal hominins, a topic that requires strong analytical skills in interpreting paleoanthropological data. The study is conducted through a qualitative approach using a literature review method that examines scientific publications, empirical reports, and theoretical discussions related to the implementation of inquiry in biological anthropology education. The analysis focuses on patterns of inquiry syntax application, the use of fossil data representations, and their contribution to the development of students’ scientific process skills. The synthesized findings indicate that guided inquiry improves students’ understanding of early bipedal traits while strengthening their abilities in observation, question formulation, data classification, and evidence-based conclusion drawing. The literature also notes increased learning motivation and scientific attitudes when inquiry is implemented in a structured manner, even without direct laboratory-based fossil analysis. This paper concludes that guided inquiry is an effective pedagogical strategy for developing scientific literacy and enhancing students’ interpretative abilities regarding human evolutionary evidence.